Explanation of Epistemology in Caring Thinking from Matthew Lipman's Perspective - Izadi Shaldehi , Majid; Salimi, Ladan; Rasouli , Seyyedeh Esmat (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The present study was conducted to explain epistemology in caring thinking from Matthew Lipman's perspective.Methods and Materials: The research method, based on its objective, was fundamental; based on the type of data, it was qualitative; based on the data collection time, it was cross-sectional; and based on the data collection method and research methodology, it was a meta-synthesis in the qualitative section. The statistical population of this study included scientific documents and resources such as specialized books, conducted research, dissertations, and articles on the philosophical foundations of caring thinking from Matthew Lipman's perspective and its educational implications, obtained from scientific databases and academic and organizational experts. The study's sampling process consisted of two sections. First, in the systematic literature review, a non-random purposive sampling method was used to select the theoretical foundations and research background based on entry criteria (a 27-item checklist following the PRISMA model). In the expert interview section, a non-random purposive sampling method was also used to select interviewees based on the research entry criteria (as specified in the target population section), and 25 interviewees were considered based on the principle of theoretical saturation. In this study, for the systematic review section, document analysis was used as the data collection tool, aligned with the research approach of systematic literature review and the review of national-level documents. In the interview section, semi-structured interviews were conducted. Additionally, a model validation questionnaire was used to assess expert opinions on the model’s external validity. To calculate validity, a 27-item checklist based on the PRISMA model was employed. Additionally, Cohen’s kappa coefficient was used to calculate reliability, which was confirmed. In the interview section, the credibility criterion was applied. The data analysis method in this study was theoretical coding, derived from thematic analysis using MAXQDA software.Findings: The findings indicated that the philosophical foundations of caring thinking, based on Matthew Lipman's perspective, include ontological, anthropological, epistemological, and axiological dimensions. Furthermore, the results showed that the educational implications of the philosophical foundations of caring thinking from Matthew Lipman’s perspective encompass acceptance and attention to diversity, focus on interpersonal relationships, respect for oneself and others, development of self-awareness, and enhancement of communication and problem-solving skills.Conclusion: The study highlights the philosophical foundations of caring thinking from Matthew Lipman’s perspective, emphasizing logical thinking, adaptability, and philosophical dialogue. Caring thinking fosters critical reflection, creativity, and adaptability, enhancing education by integrating emotional intelligence, ethical reasoning, and comprehensive cognitive development for lifelong learning.